Deskripsi Gerak dan Lagu Pada Anak Usia 5-6 Tahun - R. Amasi, Rahmatillah; Laiya, Sri Wahyuningsi; Rawanti, Sri (Jambura Early Childhood Education Journal, 2024)
This research aims to describe the movement and songs of Group B children at TK Cempaka Kindergarten in Batudaa District, Gorontalo Regency. This descriptive research used a survey method with data collection techniques involving a questionnaire. The population and sample consisted of 24 Group B children from TK Cempaka Kindergarten in Batudaa District, Gorontalo Regency. The instrument was a questionnaire, and data analysis was conducted descriptively in percentage form. Based on the analysis, it was found that (1) the percentage of Movement and Songs in Group B children at TK Cempaka Kindergarten in Batudaa District, Gorontalo Regency, based on developmental indicators, showed that children were able to recognize body parts through movement and songs such as "Kepala Pundak Lutut Kaki" with a category of Developing as Expected (BSH) at 58%. (2) the percentage of developmental progress in children's ability to mimic farmers planting corn through movement and songs, for example, "Menanam Jagung," with a category of Developing as Expected (BSH) at 58%. (3) the percentage of developmental progress in children's ability to express something not belonging to them through movement and songs such as "Topi Saya Bundar" with a category of Developing as Expected (BSH) at 60%. (4) the percentage of developmental progress in children's ability to recognize body parts through movement and songs such as "Dua Mata Saya" with a category of Developing as Expected (BSH) at 65%. (5) the percentage of developmental progress in children's ability to appreciate nature through movement and songs such as "Naik-naik Ke Puncak Gunung" with a category of Developing as Expected (BSH) at 63%. (6) the percentage of developmental progress in children's ability to recognize the colors of the rainbow through movement and songs such as "Pelangi-pelangi" with a category of Developing as Expected (BSH) at 66%. The Movement and Songs of Group B Children at TK Cempaka Kindergarten in Batudaa District, Gorontalo Regency, are categorized as "Developing as Expected" (BSH).